Genetic Diversity of ï«-Casein Gene of Friesian-Holstein Dairy Cattle using Restriction Fragment Length Polymorphism Technique - Widayanti, R; Artama, WT; Subagyo, S; Winarso, D (ANIMAL PRODUCTION, 2008)
The objective of the research was to evaluate the genetic varieties of kï-Casein gene of Holstein Friesian (HF) in Koperasi Unit Desa (KUD) Karangploso, Dau, Ngantang and Pujon, Malang, East Java by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism Analysis (PCR-RFLP) using Pst-l. Â The research used Holstein Friesian dairy cows raised by farmers of KUD Karangploso, Dau, Ngantang and Pujon, Malang, East Java. The blood samples were collected from 29 cows. The research activities were carried out by collecting cowâs blood, DNA extraction, and DNA amplification with PCR. PCR products were digested with Pst-l enzyme restrictions, then allele genes of k-ïCasein were identified. The frequency of allele and genotype of ïk-Casein gene were calculated by Hardy-Weinberg. The results showed that cows raised by farmers of KUD Karangploso, Dau, Ngantang and Pujon, Malang-East Java had two alleles k-ïCasein polymorphism, i.e. allele A (0,74) and B (0,26); therefore, two genotypes existed including AA (0,55) and AB (0,38). It can be concluded that genetic diversity of k-Casein gene existed in Holstein-Friesian dairy cows raised by farmers of KUD Ngantang, Pujon, Dau and Karangploso, Malang, East Java. (Animal Production 10(1): 1-4 (2008)Â Key Words: Pst-1, k-casein gene, PCR-RFLP